Cyclodepsipeptides - Potential Drugs and Lead Compounds in the Drug Development Process - Lemmens-Gruber, R.; Kamyar, M. R.; Dornetshuber, R. (Current Medicinal Chemistry, 2009)
Cyclodepsipeptides show an interesting spectrum of biological activity. Members of this new class of potential drugs may also serve as lead compounds for more pharmacologically potent and toxicologically safe derivatives. Some of these natural products and (semi-)synthetic derivatives have already been evaluated in clinical trials. A common feature of cyclodepsipeptides is their ionophoric properties. However, their pharmacologically relevant action does not seem to correlate with this feature; rather it is based on interactions with distinct cellular compartments and signal transduction pathways. Cyclodepsipeptides, which are currently being evaluated in clinical trials, are used in refractory cancer therapy, usually in combination with other cytotoxic drugs. A series of cyclooctadepsipeptides, however, shows a completely different spectrum of biological activity, namely, potent anthelmintic properties. A number of cyclodepsipeptides have been well characterized in vitro and in vivo, and interesting modes of action, such as antiplasmodial, antiviral, insecticidal, cytotoxic, and antiproliferative properties have been observed. Whether these natural products will be of benefit for patients must be evaluated in clinical trials. Recently, a number of cyclodepsipeptides from marine sponges, bacteria and fungi have been identified. Subsequent structural determination revealed unique structural features within some of these compounds. It was suggested that the cyclic depsipeptide structure is important for the biological activity because the linear homologues were inactive. The scope of activity of these newly isolated natural products spans a range from cytoprotective activity against HIV-1 infection, growth inhibitory effects toward cancer cells, and antimycobacterial, and antimalarial activity.
Keywords: depsipeptide